Bioactivity based evaluation of medicinal plant Solanum villosum (Mill.) in south India against diethylnitrosamine induced hepatocellular carcinoma (Funded Work) - Dr. R. VENKATESH,; Dr. K. KALAIVANI, (International Journal of Pharma and Bio Sciences, 2019)
This research tries to evaluate and analyse the anticancer potential of Solanum villosum leaf extract against diethylnitrosamine (DEN) induced hepatocellular carcinoma in experimental rats. The biochemical analysis, tumour markers, hematological parameters, intermediary metabolic enzymes, molecular genetic analysis and histopathological studies were carried out in a systematic manner and it was statistically compared between the different experimental groups. Administration of DEN (Diethylnitrosamine) induced hepatocellular carcinoma it is confirmed based on biochemical parameters and histopathological observations. After the administration of EESV (ethanolic extract of Solanum villosum) supplement has significantly attenuated these alterations, thereby showing potent anticancer activity of Solanum villosum leaf extract. These findings suggest that EESV reduce hepatic cell damage, and protects the metabolic system against DEN-induced hepatocellular carcinogenesis.